1996
DOI: 10.1103/physreve.54.2334
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of integrate and fire oscillators with global coupling

Abstract: In this article we study the behavior of globally coupled assemblies of a large number of Integrate and Fire oscillators with excitatory pulse-like interactions. On some simple models we show that the additive effects of pulses on the state of Integrate and Fire oscillators are sufficient for the synchronization of the relaxations of all the oscillators. This synchronization occurs in two forms depending on the system: either the oscillators evolve "en bloc" at the same phase and therefore relax together or th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 61 publications
1
23
0
3
Order By: Relevance
“…Networks of nonidentical oscillators were analyzed in Ref. 3, with simplified models, and synchronization properties were studied. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Networks of nonidentical oscillators were analyzed in Ref. 3, with simplified models, and synchronization properties were studied. In Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Although different processes can underlie synchronization (see Pikovsky, Rosemblum, & Kurths, 2001& Strogatz, 2003 for reviews), spontaneous phase synchrony has been observed among very different entities in a broad range of physical, biological and social systems ranging from Josephson junctions (Tsygankov & Wiesenfeld, 2002) to fireflies (Winfree, 1967), sinoatrial pacemakers (Michaels, Matyas, & Jalife, 1987), columns in the visual cortex (Gray, Konig, Engel, & Singer, 1989) and firing neurons (Nunez, Panetsos, & Avendano, 2000). Following on Huygens's analysis of two clocks synchronizing on a wall (Bennett, Schatz, Rockwood, & Weisenfield, 2002;Hugenii, 1673), many studies have since framed the problem of mutual synchronization in terms of a network of oscillators whose individual behavior is altered by nearest neighbor interactions (Bottani, 1996;Kuramoto, 1984;Pikovsky et al, 2001;Strogatz, 2003;Winfree, 1967Winfree, , 1980. The coordination dynamics of human brain and behavior has proven no exception to the principles of self-organized synchronization (Kelso, 1995;Fuchs, Kelso, & Haken, 1992;Kelso, Bressler, Buchanan, de Guzman, Ding, Fuchs, & Holroyd, 1992;Kelso, Fuchs, Lancaster, Holroyd, Cheyne, & Weinberg, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, systems with global coupling, where every oscillator interacts equally with every other, tend to fall into perfect synchrony. Rigorous convergence results have been proven for this case [20,[22][23][24][25]. But the techniques used previously have not revealed much about the transient dynamics leading up to synchrony-the opening and middle game, as opposed to the end game.…”
mentioning
confidence: 89%